Applying the values of Pancasila in shaping the character of elementary school students - Nabila Mutiara Bilqis; Maisyaroh Maisyaroh; Mustiningsih Mustiningsih (Himpunan Pengembang Kurikulum Indonesia, 2026)
Improving the quality of human resources is a key focus of national development, particularly at the elementary school level. This study aims to examine the application of the noble values of Pancasila in the character formation of students at SDIT Ahmad Yani in Malang City and at SDN 1 Landungsari in Malang Regency. Using a qualitative approach with a multi-site case study design, this study collected data through observation, in-depth interviews, and documentation. Data were analyzed using the interactive analysis model of Miles and Huberman. The main focus of this study is the application of the six dimensions of the Profil Pelajar Pancasila, namely faith, piety, mutual cooperation, independence, critical thinking, and creativity. The results show that SDIT Ahmad Yani applies character education with a more structured and intensive approach, particularly in the dimensions of faith, piety, and creativity. On the other hand, SDN 1 Landungsari applies Pancasila values in a more routine, traditional manner, while remaining consistent in its religious and social activities. These differences indicate that the success of character education implementation is strongly influenced by each school's resources and context. This research provides an important contribution in understanding the need for a holistic and participatory approach in strengthening Pancasila-based character education. Abstrak Peningkatan kualitas sumber daya manusia menjadi salah satu fokus utama pembangunan nasional, khususnya di jenjang sekolah dasar. Penelitian ini bertujuan untuk mengkaji penerapan nilai-nilai luhur Pancasila dalam pembentukan karakter murid di SDIT Ahmad Yani Kota Malang dan SDN 1 Landungsari Kabupaten Malang. Menggunakan pendekatan kualitatif dengan desain studi kasus multusitus, penelitian ini melibatkan observasi, wawancara mendalam, dan dokumentasi untuk mengumpulkan data. Data dianalisis dengan model analisis interaktif dari Miles dan Huberman. Fokus utama penelitian ini adalah penerapan enam dimensi Profil Pelajar Pancasila, yaitu beriman, bertakwa, bergotong royong, mandiri, berpikir kritis, dan kreatif. Hasil penelitian menunjukkan bahwa SDIT Ahmad Yani menerapkan pendidikan karakter dengan pendekatan yang lebih terstruktur dan intensif, khususnya dalam dimensi beriman, bertakwa, dan kreatif. Di sisi lain, SDN 1 Landungsari menerapkan nilai-nilai Pancasila dengan cara yang lebih rutin dan tradisional, meskipun tetap konsisten dalam kegiatan keagamaan dan sosial. Perbedaan ini mengindikasikan bahwa keberhasilan implementasi pendidikan karakter sangat dipengaruhi oleh sumber daya dan konteks masing-masing sekolah. Penelitian ini memberikan kontribusi penting dalam memahami perlunya pendekatan holistik dan partisipatif dalam penguatan pendidikan karakter berbasis Pancasila. Kata Kunci: berpikir kritis; kreativitas; nilai Pancasila; pendidikan karakter; Profil Pelajar Pancasila